Asymmetric price adjustment and the effects of structural reforms and low demand in the gasoline market: The case of Greece - Z. Bragoudakis; Dimitrios Sideris (Journal of Applied Economics, 2021)
The pricing mechanism in the gasoline market has often been the subject of public debate in Greece during the crisis years. Inefficient pricing could imply oligopolistic practices and losses to consumers' welfare. A way to test for inefficient pricing, is by testing for asymmetries in the adjustment of domestic gasoline prices to world oil price changes. The present paper tests for asymmetric adjustment of gasoline prices to oil price variations in the Greek market and examines whether the structural reforms that took place in the post-2010 period had any impact on the functioning of the market. The analysis applies a consistent threshold cointegration technique and makes use of the most recent observations at the lowest frequency available. The results provide evidence in favour of symmetric behaviour, just for the recent period. This may reflect competitive behaviour by suppliers who had to interact in a new institutional framework following the reforms.
Keywords: 330; Asymmetry; crude oil; gasoline; threshold cointegration